STUDY OF SEA LEVEL RISE USING SATELLITE ALTIMETRY DATA (A case study: Sea Of Semarang) - Cahyadi, M. Nur; Jaelani, Lalu Muhamad; Dewantoro, Aryasandah H. (Departemen Teknik Geomatika ITS, 2016)
Sea level rise was one thing that can threaten human life, especially those living coastal region. Not only the coastal areas threatened by sea level rise but small islands outermost region of Indonesia also threatened by sea level rise and almost lost due to sea level continued to rise from year to year. On the island of Java in particular, there are several cities that are experiencing serious problems of sea level rise call Jakarta, Semarang, Pekalongan, Tuban and Surabaya. Sea level rise that occurred in cities is caused by rising global temperatures resulting in melting glaciers and ice there dikutub, consequently the volume of water in the sea increased dramatically and lead to sea level rise. It is also exacerbated by the rate of decline in soil is very high, namely the city of Semarang, the rate of decline in soil between 8-13 cm / year. So it is very threatening to the survival of people living in coastal areas, therefore the observation of sea level rise should continue to be observed annually. One of the emerging technologies and widely used for observing the sea level rise that satellite altimetry. In this study used satellite altimetry Jason-1 to observe the rate of sea level rise in the region Semarang in 2009 to 2011 to obtain prediction with mathematical methods to determine the annual rate for the next year. On this study, large sea level rise semarang is 12.83 mm / year.